Persepsi Kualitas Mahasiswa Program Studi DIII Akuntansi Polines Selama Praktek Kerja Lapangan (PKL) di Industri - Moh.Hasanudin Marliyati; Sri Murtini; Resi Yudhaningsih; Retno Retno (Politeknik Negeri Semarang, 2018)
This research aimed at exploring the quality of accounting diploma students during their internship program in industries. The term of student’s quality described in this research isexplained using 5 main components as follows: (1) communication skills (2) teamwork (3) independence (4) creativity (5) accounting and information technology (IT)-related skills. The research’s sample is industries where students of Diploma in Accounting of State Polytechnic of Semarang (SPS) took their intership and the students themselves whom have completed their internship program for three months in various institutions such as private enterprises, state owned enterprises, local government offices spread out around Central Java. The data on this research is time series data taken from 2015 to 2016 and was collected using questionnaires from the corresponding industries about the students competencies both hard skills and soft skills. Data was scored using Likert scale, ranges from Poor (1) to Excellent (5) and analyzed using statistic descriptive. The result showed that average students’ quality during their internship was good. Among the 5 skills observed, the corresponding industries ranked teamwork skills as the highest, followed by independence, creativity, communication skills and the accounting and IT -related skills. It is expected that the result can be used for future development of Accounting Program Study of SPS.